Economic Sustainability and Challenges of Micro and Small Enterprises in the One Town, One Product Program of the Department of Trade and Industry - Teresita Tawingan (Research Synergy Foundation, 2024)
This study examined economic sustainability in micro and small enterprises (MSEs) participating in the